Comparison of Breast Milk Production Between BOM Methods (Breast Care, Oxytocin Massage, Mermaid Technique) With Breast Care in Postpartum Mothers in Takeran District, Indonesia - Alvy Nour Khasana; Teta Puji Rahayu; Nurlailis Saadah; Sunarto (International Journal of Advanced Health Science and Technology, 2023)
Breast milk is a perfect food both in quality and quantity. Many factors affect exclusive breast feeding, one of which is the lack of maximum milk production. Post partum mothers must have the enthusiasm to give exclusive breast feeding to their babies. With proper breast feeding management, maximum results will be obtained. The purpose of this study was to determine the difference in the amount of breast milk production between the BOM method (Breast Care, Oxytocin Massage, Mermaid Technique) and Breast Care for post partum mothers in the Work Area of the Takeran Health Center. The type of research is Quasi Experiment with Post Test Only Control Group Design. The population is all pregnant women in the work area of the Takeran Health Center whose expected delivery day is in March-April 2022 as many as 32 pregnant women. All affordable populations were sampled. The independent variable is BOM and Breast Care and the dependent variable is breast milk production. Data analysis used the Mann Whitney statistical test with a significance level of p <0.05. In the experimental group using the BOM method, there were 13 respondents (81.3%) whose breast milk production was smooth and 3 respondents (18.7%) whose milk production was not, while in the control group using the Breast Care method 14 respondents ( 87.5%)whose milk production is not smooth and 2 respondents (12.5%)whose milk production is smooth. The results of the Mann Whitney test obtained a significance value of 0.000 < = 0.05. The conclusion of the study is that there is a difference in the amount of milk producti n between the BOM method and breast care. The BOM method can be used as an alternative to non-pharmacological therapy to increase breast milk production in post partum mothers so that it can increase the success of exclusive breast feeding.